2011
DOI: 10.1039/c0cc03946b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-mesoporous Janus nanoparticles

Abstract: Novel multifunctional magnetic-mesoporous Janus particles with controlled aspect ratio were developed by a simple one-step synthesis approach. Due to their superior magnetic properties and well-defined pore structures, these particles will be important in drug delivery, molecule targeting, cellular imaging, and as building blocks for the assembly of complex nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 23 publications
3
95
1
Order By: Relevance
“…Janus magnetic particles, meanwhile, form chiral chains, staggered chains, or doubled chain-like structures as well as linear chain structures, depending on their internal structure [9,[18][19][20][21][22][23]. In the presence of a rotating magnetic field, magnetic Janus colloids are found to form unusual crystal structures [24].…”
Section: Introductionmentioning
confidence: 99%
“…Janus magnetic particles, meanwhile, form chiral chains, staggered chains, or doubled chain-like structures as well as linear chain structures, depending on their internal structure [9,[18][19][20][21][22][23]. In the presence of a rotating magnetic field, magnetic Janus colloids are found to form unusual crystal structures [24].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al synthesized various CPs nano-particles such as PANI, poly(o-phenylenediamine), Ag@poly (m-phenylenediamine), poly(m-phenylenediamine), poly(p-phenylenediamine) and polynaphthylamine which were applied in the fluorescence detection of nucleic acid [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The results showed that these nano-particles can absorb and quench dye-labeled single-stranded DNA (ssDNA) very effectively.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, conducting polymers (CPs) such as: polyaniline (PANI), polythiophene (PTH), polyparaphenylene (PPP) and polypyridine (PPY) are widely used in fluorescent probes [27][28][29][30][31], adsorbents [32][33][34][35][36][37][38][39][40][41][42][43], electrode materials [44][45][46][47] and photocatalysis [48][49][50][51][52][53]. Sun et al synthesized various CPs nano-particles such as PANI, poly(o-phenylenediamine), Ag@poly (m-phenylenediamine), poly(m-phenylenediamine), poly(p-phenylenediamine) and polynaphthylamine which were applied in the fluorescence detection of nucleic acid [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…18 Besides, ligands are also used to bridge the two distinct parts to form a Janus structure. 19 To produce Janus nanoparticles with single material phase but two different surface properties, Pickering emulsion was developed by Granick and coworkers. 11,20 Nanoparticles can be adsorbed onto the surface of droplets to stabilize an emulsion, namely, Pickering emulsion.…”
Section: Inorganic Janus Particlesmentioning
confidence: 99%